Energy Consumption Reduction Strategies for Plug-In Hybrid Electric Vehicles with Connected Vehicle Technology in Urban Areas. Issue 1 (January 2014) - Bhavsar, Parth; He, Yiming; Chowdhury, Mashrur; Fries, Ryan; Shealy, Andrew
Automobile manufacturers have introduced plug-in hybrid electric vehicles (PHEVs) to reduce fossil fuel consumption. This paper details three optimization strategies that can be used to minimize the energy consumption of PHEVs further through an information exchange between PHEVs and infrastructure agents supported by connected vehicle technology (CVT). An earlier study focused on a freeway scenario. The study reported here developed strategies for an urban scenario with frequent stop-and-go conditions. Three strategies were considered on the basis of different types of information availability with the use of CVT. Only signal timing information was available in Strategy 1; only headway information was available in Strategy 2; and both signal timing and headway information were available in Strategy 3. The performance of PHEVs that received no real-time information was used as the base case for Strategies 1, 2, and 3 to evaluate each strategy. The optimization strategies resulted in energy consumption savings that ranged from 60% to 76%. An analysis, with various levels of penetration of CVT-supported PHEVs in traffic, was conducted to demonstrate the impact of these optimization strategies with their increased market share. For a case study network, a linear trend was found between energy savings and the penetration rate of CVT-supported PHEVs. Strategy 3, in which signal timing and headway data were provided to CVT-supported PHEVs, resulted in about 31% to 35% energy savings, with a 30% penetration of CVT-supported PHEVs at the peak hour volume.